MENGUKUR DAN MENGELOLA INTELLECTUAL CAPITAL - Imam Sugeng ND (UGM, 2000)
In the postindustrial era, the success of a corporation lies more in its intellectualcapital and system capabilities than in its physical assets. The capacity to manage intellectual capital-and to convert it into useful product and servies to fast becoming the critical executive skill of the age. As a result, there has been a flurry of interest in intellectual capital, ereativity, innovation, and learning organization. However, the debate about how measure the intellectual capital still exist within the expert.